A novel linear indexing method for strings under all internal nodes in a suffix tree - Al-okaily, Anas; Tbakhi, Abdelghani (Frontiers in Bioinformatics, 2025)
Suffix trees are fundamental data structures in stringology and have wide applications across various domains. In this work, we propose two linear-time algorithms for indexing strings under each internal node in a suffix tree while preserving the ability to track similarities and redundancies across different internal nodes. This is achieved through a novel tree structure derived from the suffix tree, along with new indexing concepts. The resulting indexes offer practical solutions in several areas, including DNA sequence analysis and approximate pattern matching.